Prescription audit adjunct to rational pharmacotherapy education improves prescribing skills of medical students - AKICI, AHMET (SPRINGER HEIDELBERG, 2005)
Objective: To assess the impact of a rational pharmacotherapy (RP) teaching program during clinical pharmacology clerkship by analyzing the results of prescription audits (PAs) of the medical students. Collectively, we intended to observe the possible improvement of the students in their prescribing, problem solving and self-directed learning skills. Design: At the beginning and end of the clerkship, the students were presented with cases of uncomplicated osteoarthritis to assess their prescribing skills; format and rationality were scored. Setting: A medical school in Turkey that teaches RP to the fourth-year students in clinical pharmacology clerkship. Participants: There were 94 students of the 2002-2003 academic year in three groups and a single group of students belonging to the previous academic year tested. Of those students from the previous academic year, 26 were also analyzed a year later to demonstrate the long-term impact of the training. Main outcome measures: Prescribing skills of medical students and their opinions about PA. Results: Direct assessment via PA demonstrated that the scores for post-clerkship prescriptions were far better than those for pre-clerkship prescriptions in terms of format and rationality. Long-term assessment showed that the scores declined within a year following clerkship, but they were still higher than those of their pre-clerkship scripts. Analysis of the questionnaires revealed that the students were satisfied with PA. The majority of the students stated they had learned the general principles of RP and gained better prescribing skills, and they intended to apply most of the principles learned to their future professional lives. The script format scores of a retrospectively created PA-exempted group were significantly lower than those of the students to whom an established PA education was given. Conclusion: PA sessions were shown to be an easy and a useful method of both evaluating and reinforcing prescribing skills gained though problem-based RP education.
Keywords: prescription audit; rational pharmacotherapy; medical education; PRESENTING CLINICAL-PHARMACOLOGY; GENERAL-PRACTITIONERS; PRIMARY-CARE; FEEDBACK; IMPACT; RECOMMENDATIONS; OSTEOARTHRITIS; THERAPEUTICS; COMPETENCE; GUIDELINES